2003
DOI: 10.1093/emboj/cdg050
|View full text |Cite
|
Sign up to set email alerts
|

The Helicobacter pylori CagA protein induces cortactin dephosphorylation and actin rearrangement by c-Src inactivation

Abstract: The gastric pathogen Helicobacter pylori translocates the CagA protein into epithelial cells by a type IV secretion process. Translocated CagA is tyrosine phosphorylated (CagA P-Tyr ) on speci®c EPIYA sequence repeats by Src family tyrosine kinases. Phosphorylation of CagA induces the dephosphorylation of as yet unidenti®ed cellular proteins, rearrangements of the host cell actin cytoskeleton and cell scattering. We show here that CagA P-Tyr inhibits the catalytic activity of c-Src in vivo and in vitro. c-Src … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
227
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(250 citation statements)
references
References 60 publications
21
227
0
2
Order By: Relevance
“…It has been previously described that Src kinases are inactivated upon CagA phosphorylation that leads to tyrosine dephosphorylation of several host cell proteins (Selbach et al, 2003. However, the question was still open why CagA phosphorylation increases in sustained H. pylori infections, even though Src kinases are inactivated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously described that Src kinases are inactivated upon CagA phosphorylation that leads to tyrosine dephosphorylation of several host cell proteins (Selbach et al, 2003. However, the question was still open why CagA phosphorylation increases in sustained H. pylori infections, even though Src kinases are inactivated.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of c-Abl was only slightly increased within the first hour of infection, but strongly induced after 2 h. These different kinetics might explain why high concentrations of the c-Abl inhibitor STI571 were needed to block CagA phosphorylation whereas low inhibitor doses were sufficient to block sustained CagA phosphorylation in prolonged H. pylori infections. CagAmediated Src inactivation leads to dephosphorylation of cellular Src substrates such as ezrin and cortactin (Selbach et al, 2003, whereas H. pylori-induced c-Abl activity leads to activation of c-Abl specific substrates such as Crk proteins in successive processes. We conclude from our study that Src and c-Abl kinases play differential roles in infected epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings exclude the possibility that the CagA-SHP-2 complex is detectable only when CagA is expressed by gene transfection. In this regard, Selbach et al (60) reported that injected CagA failed to bind SHP-2 but that transfected CagA bound SHP-2 in AGS cells. In their study, bacteria-injected CagA possessed 3ϫ EPIYA (Tigr strain-derived CagA; "A-B-C" type according to the classification by Higashi et al (24)), whereas transfected CagA had 5ϫ EPIYA (NCTC11637 strain-derived CagA; "A-B-C-C-C" type).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CagA species usually vary on the number of EPIYA-C or -D repeats in the carboxyl terminus of the protein. Phosphorylated CagA has been reported to interact with and deregulate the activity of a number of intracellular effectors relating to the hepatocyte growth factor signaling pathway, such as Src homology 2-containing protein tyrosine phosphatase 2 (16), growth factor receptor bound 2 (21), carboxyl-terminal Src kinase (29), and hepatocyte growth factor receptor/cMet (13). More specifically, tyrosine-phosphorylated CagA seems to bind and deregulate the activity of Src homology 2-containing protein tyrosine phosphatase 2 via the Western CagA-specific EPIYA-C or East Asian CagA-specific EPIYA-D site and of carboxyl-terminal Src kinase via the EPIYA-A or EPIYA-B site (22).…”
mentioning
confidence: 99%